Generic Structure and Attitude of Closing Ceremony Speeches in International Seminars - Agnes Erliva; Sri Wuli Fitriati; Abdurrahman Faridi (Universitas Negeri Semarang, 2022)
Nowadays there are a lot of international seminars in various fields of subjects conducted around the world to share ideas, research results, new regulations, a new decree, new theory, and so on. Most of the time the representative of the committee in the international seminar finds it difficult to shape the best guidance for the speech text at the closing ceremony. People tend to search for other examples of closing speech to shape their closing ceremony speech text to be the better one because every speech is an opportunity to affect people’s behaviours, beliefs, or actions by the attitude. However, there is no standard called generic structure and attitude which is quite special only for closing speech type. For that reason, the research objectives are to analyse the structures and attitude resources in closing speeches; and to analyse the relationship between structures and attitudes in closing ceremony speeches through the SFL approach. This is a qualitative study that employs the theory of appraisal and a basic understanding of generic structure in the SFL perspective. There are several structures generally found in each closing speech, namely addressee, identification of the speaker, encapsulation of event, valuation of event, wish/hope, special thank, and final thank. The positive valuations are the highest attitude resources found in the closing speeches. The result of this research is benefited to ELT in which the English language teacher can enrich the types of potential generic structure of the text, especially closing speech text.